The Position of the Lebanese Shia Community on the Israeli Invasion of Lebanon in 1982 - Naeem, Prof. Dr. Ali Hussein; ali, zahara raheem (Thi Qar Arts Journal, 2024)
The military operations carried out by Palestinian armed factions against Israel from Lebanese territory were the direct cause of the Israeli invasion of Lebanon in June 1982. The invasion aimed to expel the Palestine Liberation Organization (PLO) from Lebanon, end the Syrian military presence, and establish a regime willing to sign a “peace” treaty with Tel Aviv. While the invasion achieved some of its objectives, it was met with resistance, condemnation, and denunciation on various levels, particularly from the Lebanese Shia community. The Shia community strongly opposed the invasion through statements, denunciations, and armed resistance.